Human SHC‐transforming protein 1 and its isoforms p66shc: A novel marker for prediabetes. Issue 10 (20th May 2021) - Jelinek, Herbert F; Helf, Charlotte; Khalaf, Kinda
Abstract: Aims: Prediabetes is a multifactorial condition. Current guidelines for diabetes screening recommend either the use of glycated hemoglobin (HbA1c), or blood glucose level (BGL). This research aimed to identify if p66shc a component of the Human SHC‐Transforming Protein 1 (Shc1), a mitochondrial associated oxidative stress biomarker, is significantly altered in patients with elevated BGL. Furthermore, we evaluated if inflammatory and oxidative stress markers, such as p66shc, are a useful addition to the regularly used biomarkers to increase sensitivity for identification of prediabetes. Methods: All participants attended the Diabetic Health Screening at Charles Sturt University (CSU), Australia. The cross‐sectional clinical study collected demographic and clinical variables from 346 participants and classified into control or prediabetes based on fasting BGL. Blood and urine samples were analyzed for oxidative stress and inflammation markers. Logistic regression was used to compare multidimensional diagnostic models for prediabetes, including p66shc/Shc1, to the current HbA1c‐only model in terms of sensitivity, specificity and predictive accuracy. Significance was set at P  ≤ 0.05. Results: A significant decrease of p66shc/Shc1 was determined in prediabetes compared to controls ( P  ≤ 0.05). HbA1c testing resulted in an accuracy of 62%, while adding p66shc and triglycerides increased predictive accuracy to 88.05%. When HbA1c was omitted and Shc1 was combined with 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG) and monocyte chemo‐attractant protein‐1 (MCP‐1), a predictive accuracy of 89.5% was achieved. Conclusion: Our findings showed a major improvement of sensitivity to identify prediabetes by including oxidative stress and inflammatory biomarkers underlining beneficial diagnostic information, which most likely improves prevention and early treatment options in prediabetes. Abstract : SHC‐1 is associated with oxidative stress, which in conjunction with inflammatory markers is involved in the pathogenesis of prediabetes.